1, 25‐Dihydroxyvitamin D Alone Improves Skeletal Growth, Microarchitecture, and Strength in a Murine Model of XLH, Despite Enhanced FGF23 Expression. (2nd February 2016) - Liu, Eva S; Martins, Janaina S; Raimann, Adalbert; Chae, Byongsoo Timothy; Brooks, Daniel J; Jorgetti, Vanda; Bouxsein, Mary L; Demay, Marie B
ABSTRACT: X‐linked hypophosphatemia (XLH) is characterized by impaired renal tubular reabsorption of phosphate owing to increased circulating FGF23 levels, resulting in rickets in growing children and impaired bone mineralization. Increased FGF23 decreases renal brush border membrane sodium‐dependent phosphate transporter IIa (Npt2a) causing renal phosphate wasting, impairs 1‐α hydroxylation of 25‐hydroxyvitamin D, and induces the vitamin D 24‐hydroxylase, leading to inappropriately low circulating levels of 1, 25‐dihydroxyvitamin D (1, 25D). The goal of therapy is prevention of rickets and improvement of growth in children by phosphate and 1, 25D supplementation. However, this therapy is often complicated by hypercalcemia and nephrocalcinosis and does not always prevent hyperparathyroidism. To determine if 1, 25D or blocking FGF23 action can improve the skeletal phenotype without phosphate supplementation, mice with XLH (Hyp) were treated with daily 1, 25D repletion, FGF23 antibodies (FGF23Ab), or biweekly high‐dose 1, 25D from d2 to d75 without supplemental phosphate. All treatments maintained normocalcemia, increased serum phosphate, and normalized parathyroid hormone levels. They also prevented the loss of Npt2a, α‐Klotho, and pERK1/2 immunoreactivity observed in the kidneys of untreated Hyp mice. Daily treatment with 1, 25D decreased urine phosphate losses despite a marked increase in bone FGF23 mRNA and in circulating FGF23 levels. Daily 1, 25D was more effective than other treatments in normalizing the growth plate and metaphyseal organization. In addition to being the only therapy that normalized lumbar vertebral height and body weight, daily 1, 25D therapy normalized bone geometry and was more effective than FGF23Ab in improving trabecular bone structure. Daily 1, 25D and FGF23Ab improved cortical microarchitecture and whole‐bone biomechanical properties more so than biweekly 1, 25D. Thus, monotherapy with 1, 25D improves growth, skeletal microarchitecture, and bone strength in the absence of phosphate supplementation despite enhancing FGF23 expression, demonstrating that 1, 25D has direct beneficial effects on the skeleton in XLH, independent of its role in phosphate homeostasis. © 2016 American Society for Bone and Mineral Research.